2020
DOI: 10.1680/jemmr.20.00096
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on aluminum alloys as winding materials for alternators in wind turbines

Abstract: The use of aluminum (Al) alloy substances is analyzed in this paper in order to obtain a lighter and less costly winding design without dimensional changes in electrical machines. The determination of aluminum alloy winding material, which has an electrical conductivity close to that of copper (Cu) but has a lower density, is the basis of this study. In this context, various aluminum alloy substances have been investigated. Windings with these aluminum alloy materials for a 300 kVA synchronous alternator have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The most important reason for this is that Al materials have good conductivity and are abundant and cheap around the world (Hergul et al, 2020). In addition, the cost of an Al conductor of the same resistance and length is significantly lower than the cost of a Cu conductor.…”
Section: Developingmentioning
confidence: 99%
“…The most important reason for this is that Al materials have good conductivity and are abundant and cheap around the world (Hergul et al, 2020). In addition, the cost of an Al conductor of the same resistance and length is significantly lower than the cost of a Cu conductor.…”
Section: Developingmentioning
confidence: 99%
“… [ 35 , 36 , [47] , [48] , [49] ] Wind Turbines ALUMINUM Most of a wind turbine's components, especially the nacelle, where wind energy is converted to electricity, are made of aluminum. [ 29 , [50] , [51] , [52] , [53] ] RARE-EARTH ELEMENTS (neodymium) Rare-earth elements make some of the planet's strongest and most effective magnets, allowing wind turbines to use lighter, more compact generators. [ [54] , [55] , [56] , [57] ] Batteries COBALT Cobalt is most commonly used in rechargeable battery electrodes on a global scale.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In addition, the aluminium winding structure was analysed in detail in terms of various aluminium alloys, and a comparison was made. The comparison results showed that the 1350, 2041, and 2017 types of aluminium alloys exhibited better efficiency performance than the conventional materials used in electrical machines [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of wind energy conversion systems, limited studies have been conducted on the materials used in generator windings. In [17] and [18], a wound-rotor synchronous machine (WRSM) with a power capacity of 300 kVA was designed with aluminium windings, and performance analysis was performed. By only changing the winding conductor material, the weight was reduced by nearly 12% compared to the traditional copper wound WRSM.…”
Section: Introductionmentioning
confidence: 99%